2002
DOI: 10.1002/1616-3028(20020805)12:8<513::aid-adfm513>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Dark Spot Formation and Growth in Organic Light-Emitting Devices by Controlling Pinhole Size and Shape

Abstract: We report on our in‐situ experimental observations of dark spots in organic light‐emitting diodes using optical microscopy. Uniformly sized silica microparticles are used to intentionally create size‐ and shape‐controllable pinholes on the cathode protective layer. Subsequently, the pinholes trigger the initial formation of dark spots, which we then monitor. Due to the use of particles of various diameters, we are able to linearly associate the growth rate with pinhole size. This allows us to estimate the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…3 The primary shortcoming of most OLEDs is poor environmental stability that results in nonemissive regions upon extended exposure to ambient conditions. The degradation in performance is a result of the oxidation and delamination of the metal cathode 4 and the chemical reaction of the organic layer from exposure to moisture and oxygen. OLED lifetimes can be extended by orders of magnitude by device encapsulation.…”
Section: Introductionmentioning
confidence: 51%
“…3 The primary shortcoming of most OLEDs is poor environmental stability that results in nonemissive regions upon extended exposure to ambient conditions. The degradation in performance is a result of the oxidation and delamination of the metal cathode 4 and the chemical reaction of the organic layer from exposure to moisture and oxygen. OLED lifetimes can be extended by orders of magnitude by device encapsulation.…”
Section: Introductionmentioning
confidence: 51%
“…The key issue in achieving durable flexible OLEDs on plastic substrates is to protect them from moisture and oxygen as OLEDs are very sensitive to both [13][14][15] . The luminance decay curve of the device with our new hybrid encapsulation is shown in Figure 3.…”
Section: Brief Communicationsupporting
confidence: 41%
“…These materials are highly reactive, and thus they cannot be easily solution-processed but have to be evaporated. Furthermore, humidity oxidizes these cathode layers, limiting the lifetime of OLEDs. In addition, it has been shown that already submonolayers of Ca and Ba quench the photoluminance of organic emitter materials. …”
Section: Introductionmentioning
confidence: 99%